Fixation of potassium by soil samples under various conditions - Kaila, Armi (Agricultural and Food Science, 1965)
The fixation of added potassium under various conditions was studied using soil samples collected from three layers of ten mineral soils. The type of soil ranged from finesand to heavy clay, the soil reaction from pH 3.3 to pH 6.4 (in 0.01 M CaCl2), and the total potassium content from 1.99 to 3.41 per cent. The fixation against an extraction with neutral ammonium acetate distinctly depended on the conditions used for the application of potassium: on the average, without drying the samples fixed during one hour somewhat more than 80 per cent of the amount fixed during 18 hours, when the samples were treated with KCI-solutions corresponding to 2.5 me K/100 g soil. Drying the suspension at 80°C resulted in a fixation 1.2 to 4.1 times as high as that under the »wet» conditions within one hour. The results of these two methods were not particularly closely correlated (r = 0.73***). The results of the »dry» method were found to be of the same order as the fixation of potassium in samples incubated for three months at room temperature. The results of the »dry» fixation were positively correlated with the pH (r = 0.75***) and negatively correlated with the contents of organic carbon (r = —0.63***) and exchangeable potassium (r = —0.40*), but they were not correlated with the contents of clay or the acid soluble potassium. Under the »wet» conditions the relative fixation generally decreased with an increase in the application of potassium, but there were samples which fixed a rather low but almost equal portion of all the applications from 0.625 to 40 me K/100 g soil. The fixation from the highest addition was correlated with the clay fraction <0.6 μ, but not with the coarser clay, whereas the fixation from the lowest application was not correlated with the clay content. Particular attention was paid to the intensive fixation of potassium by a finesand soil (84 to 91 per cent of the applications of 2.5 to 0.615 me K/100 g soil under wet conditions), and some silt soils. When 40 me K/100 g was added these samples fixed amounts corresponding to 26 to 61 me K/100 g of clay, which may be taken to indicate that in these soils also the coarser fractions may be associated with the fixation. The fixation of potassium under the »wet» conditions by samples adjusted to various lime and potassium status in incubation experiments or in field trials was studied. Usually liming increased the fixation, although the effect was not always marked. Application of potassium salts tended to decrease the fixation capacity. When potassium had been applied at a high rate, the effect of liming on the fixing appeared to be almost negligible.